2018
DOI: 10.1002/cnr2.1141
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing delayed presentation of breast cancer at a tertiary care hospital in Pakistan

Abstract: Background: Breast cancer is the leading cause of death despite the continuous development of newer and more effective modalities of treatment for breast cancer.In Asia, Pakistan has the highest rate of breast cancer. Breast cancer treatment shows better prognosis when it is diagnosed at an early stage, but mortality increases significantly with delayed diagnosis and advanced stage of disease. Delay in diagnosis and nonavailability of treatment are the major factors responsible for advanced stage and low survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…29 While exploring reasons of delay in diagnosis of breast carcinomas in Pakistan investigators also found that 32.6% delays were attributed to the lack of accessibility of medical care facility. 30 Many other findings confirmed that in the developing countries, lack of cognizance and familiarity of symptoms of breast malignancies along with the poor education level, and lack of accessibility of health centers are strongly associated with the delays of presentation of BC. 31,32 Another significant finding of the current study was that 86% of the respondents were hesitant in visiting male doctors for BC screening.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 71%
“…29 While exploring reasons of delay in diagnosis of breast carcinomas in Pakistan investigators also found that 32.6% delays were attributed to the lack of accessibility of medical care facility. 30 Many other findings confirmed that in the developing countries, lack of cognizance and familiarity of symptoms of breast malignancies along with the poor education level, and lack of accessibility of health centers are strongly associated with the delays of presentation of BC. 31,32 Another significant finding of the current study was that 86% of the respondents were hesitant in visiting male doctors for BC screening.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 71%
“…The clinical staging of the cancer in these patients T3N1M0 (31.5%), T4N0M0 (14.6%), T3N0M0 (12.4%) and T3N2M0 (11.2%). 82 A study from Nepal showed that out of 114 patients with breast cancer, the majority of women were aged between 41–50 years. Regarding receptor status, the majority (64.0%) were Estrogen receptor (ER) and Progesterone receptor (PR) negative, 21.9% were both ER and PR positive, and 9.6% were ER negative and PR positive, while 4.4% of patients were ER positive and PR negative.…”
Section: Resultsmentioning
confidence: 99%
“…These stages comprised various factors such as the patient's sociodemographics, previous history, interpretation of the breast symptoms, types of symptoms, knowledge, attitudes, and practices toward breast symptoms, which were analyzed in most previous studies [4,6,8,9,11,[13][14][15]. Lower educational level [16] and lack of knowledge [17] were associated with delayed presentation of breast cancer.…”
Section: Discussionmentioning
confidence: 99%